Hot-substrate assisted deposition for Cs-rich α-Cs1-xFAxPbI2Br (0 ≤ x ≤ 0.4) films. (15th May 2022) - He, Qinghe; Jiang, Zhikang; Li, Deguan; Tian, Nan; Yao, Disheng; Zheng, Guoyuan; Wang, Jilin; Zhou, Bing; Long, Fei
Highlights: Cs-rich pure α-Cs1-x FAx PbI2 Br (0 ≤ x ≤ 0.4) Films were firstly synthesized by hot-substrate assisted deposition method. The humidity stability and PCE of the CsPbI2 Br were significantly improved by the incorporation of FA. α-Cs1-x FAx PbI2 Br (0 ≤ x ≤ 0.4) still maintained good thermal and UV-irradiation stability. Abstract: The mixed cation FAx Cs1−x PbI2 Br has shown great promise for the top subcell of tandem solar cells owing to its improved thermal and moisture stability. However, most studies of FAx Cs1−x PbI2 Br focus on FA-rich perovskites. Duo to the phase separation when Cs > 30%, there is still room for improvement of Cs-rich FAx Cs1−x PbI2 Br. In this work, by hot-substrate assisted deposition, Cs-rich α-Cs1-x FAx PbI2 Br (0 ≤ x ≤ 0.4) films without impure phase were synthesized. Compared with α-CsPbI2 Br film, the humidity stability of α-Cs1-x FAx PbI2 Br (0 ≤ x ≤ 0.4) films was effectively enhanced. The highest power conversion efficency of 12.3% with open-circuit voltage ( Voc ) of 1.16 V, current intensity ( Jsc ) of 14.5 mA/cm −2 and fill factor of 72.3% in α-Cs0.7 FA0.3 PbI2 Br solar cell was achieved. The α-Cs1-x FAx PbI2 Br (0 ≤ x ≤ 0.4) films after FA incorporation still maintain good thermal and UV-irradiation stability. It showed a great potential of the Cs-rich perovskite for future application.